Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa) - Rodrigues, Daniela F.s.; Navia, Denise; Oliveira, Anibal R.; Ferragut, Francisco; Flechtmann, Carlos H. W. (Zootaxa, 2017)
Two new eriophyoid mite species are described from the cocoa tree, Theobroma cacao L. (Malvaceae) – the Diptilomiopidae Davisella trevisani n. sp. Rodrigues, Navia & Oliveira, from Brazil; and the Eriophyidae Tetra theobromae n. sp. Rodrigues, Navia & Oliveira, from Costa Rica. The new Davisella species presents an enlarged subcylindrical tubercle bearing pedipalp genual seta d, a novel structure for eriophyoid mites; its functional morphology was discussed. The new Tetra species is the third in this genus described from plants of the Malvaceae. A closer look at Shevtchenkella biseta (Nalepa), described from the Malvaceae Hibiscus rosa-sinensis L., showed its taxonomic assignment to the Phytoptidae, Sierraphytoptinae and raised a hypothesis on its synonymy.